2014
DOI: 10.1016/j.yrtph.2014.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the number of fish in bioconcentration studies with general chemicals by reducing the number of test concentrations

Abstract: Fish bioconcentration test guidelines generally require that bioconcentration factors (BCFs) are determined at two exposure concentrations. However, recent revisions to the OECD test guideline for bioconcentration testing (TG 305) provide the option to use only one exposure concentration, when justification is provided, although two concentrations may still be required for some regulatory purposes. Recently, this justification has been demonstrated for plant protection product active ingredients. To determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 7 publications
(7 reference statements)
0
16
0
Order By: Relevance
“…The time and resources necessary to support this approach run counter to the demands being faced at present. Furthermore, there is mounting pressure to minimise animal usage and to use animal-free approaches in initial testing strategies, where possible [2][3][4][5]. For many years, assays using cell lines derived from fish have been proposed as alternatives to animal use in aquatic toxicity testing with excellent reviews on the topic available [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The time and resources necessary to support this approach run counter to the demands being faced at present. Furthermore, there is mounting pressure to minimise animal usage and to use animal-free approaches in initial testing strategies, where possible [2][3][4][5]. For many years, assays using cell lines derived from fish have been proposed as alternatives to animal use in aquatic toxicity testing with excellent reviews on the topic available [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The United Kingdom's National Centre for the Replacement, Refinement and Reduction of Animals in Research (NC3Rs) initiated a project to determine whether BCF values are dependent on concentration. This project consisted of retrospective data analyses on publicly available data for 55 PPP active substances and 236 general chemicals, comparing experimental fish BCF values obtained at 2 test concentrations (Creton et al 2013;Burden et al 2014). These analyses showed that there is no statistically significant difference between BCF values generated at low and high concentrations, suggesting that the BCF value is largely independent of test concentration (Figure 1).…”
Section: Referencesmentioning
confidence: 99%
“…The views or statements expressed in this publication do not necessarily represent the views of the organizations with which the authors are affiliated, and those organizations cannot accept any responsibility for such views or statements. Creton et al (2013) and Burden et al (2014). BCF ¼ bioconcentration factor; PPP ¼ plant protection product.…”
Section: Referencesmentioning
confidence: 99%
“…2,000 L/kg). Figure based on data from Creton et al (2013) and Burden et al (2014). BCF ¼ bioconcentration factor; PPP ¼ plant protection product.…”
Section: Referencesmentioning
confidence: 99%